The Color Purple? Perspectives of Canadian Parents of Adopted Children from China - Bian, Fang; Blachford, Dongyan; Durst, Douglas (Journal of Comparative Social Work, 2015)
During the past two decades, Canadian parents have been regularly adopting infants from China, and have been facing a confusing dilemma on how to introduce their children’s Chinese heritage and language. The aim of this qualitative study is to uncover the beliefs and attitudes of the adopting parents about how to best promote a healthy identify development that includes their Chinese background. Using in-depth interviews, 19 parents of 14 adopted children explored their beliefs about incorporating the Chinese heritage in the development of their girls. The findings reveal that some parents feel that it is best to emphasize Canadian culture - “she is just Canadian.” Some parents feel that it is best to leave it alone and allow the children to choose their “identity” – “she has both feet in both worlds”, whereas, other parents are proactive by introducing Chinese heritage and culture to their children at an early age. Some parents feel that their children created a new identity with the “color purple” – a hybrid and new culture that combines both their Chinese background with a mainstream Canadian lifestyle.